The Ilocano Psychology in Selected Ilocano Short Stories : N/A - NAIDAS, MICHAEL (11th International Scholars Conference, 2024)
Using a thematic approach in analyzing qualitative data, the study determined the values embedded in 16 Ilocano short stories. Aided by the tenets of Cultural Studies, the study focused on how the stories mirror Ilocano values. Eleven themes (values) emerged as a result of the analysis done on the short stories, which were further grouped into three categories. Under moral /ethical values: religiosity, honesty and patience. For cultural/traditional values: courteous, frugal, resourceful and hardworking; while for social values, friendly, helpful, party-lover and having a sense of “bain” were identified. By looking into these stories, it is safely assumed that the Ilocano identity is something positive, since all the values mentioned connotes a positive meaning. It can also be said that it is these values which shape the Ilocano identity, the true soul of the Ilocanos—their psychology. Thus, as an extension, the researcher recommends looking into other short stories and other literary genres using relevant literary or sociological theories to validate the findings of this study.